Thermography research in diabetic foot: insights from a Scopus-based bibliometric study - Zakaria, Shukriah Aqilah; Low, Chooi Leng; Kow, Ren Yi; Zakaria@Mohamad, Zamzuri; Abidin, Mohd Radhwan; Che Ahmad, Aminudin; Ahmad, Muhammad Wafiuddin; Zulkifly, Ahmad Hafiz; Sulaiman, Ahmad Syahrizan (Springer Nature, 2024)
Diabetic foot problems are among the most debilitating complications of diabetes mellitus. These problems incur significant economic costs and reduce quality of life. The integration of thermography technology in the screening and management of diabetic foot problems has been proven to be successful in recent years. By detecting changes in temperature, thermography helps identify early infections and assists in patient monitoring. These early successes have inspired more research and publications in this field. To date, a comprehensive bibliometric analysis of thermography-related research on diabetic foot using the Scopus database has not been conducted. This bibliometric analysis aims to fill this gap by reviewing the Scopus database from its inception until 2023 to examine the literature on thermography-related research on diabetic foot. A total of 342 articles met the selection criteria and were included in this analysis. The number of articles in this field remained low until the 2010s, when there was a sudden surge of interest that prompted numerous publications. Authors from the USA contributed the highest number of articles and had the greatest scholarly impact in this field. Despite the major contribution from the USA, there were numerous collaborations between various countries, underscoring the importance of international collaboration in advancing research and exchanging knowledge.